2020
DOI: 10.1080/13546783.2020.1781691
|View full text |Cite
|
Sign up to set email alerts
|

Errors, fast and slow: an analysis of response times in probability judgments

Abstract: Based on the Dual-Process Diffusion Model, we tested three hypotheses about response times of errors and correct responses in probability judgments. We predicted that correct responses were (1) slower than errors in the case of conflicting decision processes but (2) faster than errors in the case of alignment; and that they were (3) slower in the case of conflict than in the case of alignment. A binary-choice experiment was conducted in which three types of decision problems elicited conflict or alignment of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Contrary to our expectations, we found a tendency that decisions exhibiting a bias take longer than rational decisions. This finding is in accordance with some observations in the recent literature (De Neys & Glumicic, 2008; Ludwig et al., 2020; Pennycook & Thompson, 2012), which showed that correct answers in alignment with intuitive responses are generated rapidly. However, these effects were rarely studied in the context of the ratio bias.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Contrary to our expectations, we found a tendency that decisions exhibiting a bias take longer than rational decisions. This finding is in accordance with some observations in the recent literature (De Neys & Glumicic, 2008; Ludwig et al., 2020; Pennycook & Thompson, 2012), which showed that correct answers in alignment with intuitive responses are generated rapidly. However, these effects were rarely studied in the context of the ratio bias.…”
Section: Discussionsupporting
confidence: 93%
“…An exception is Ludwig et al. (2020), but in their research, the ratio bias was one type of problems in which this result did not hold.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous research argued that decision times indicated decision difficulty (Achtziger and Alós-Ferrer 2014;Ludwig, Ahrens, and Achtziger 2020;Schotter et al 2010). If zero outcomes were processed more easily than other gamble attributes, decisions should be quicker for lotteries with zero outcomes (Types IV and V) compared to lotteries without zero outcomes (Types I-III).…”
Section: Decision Time and Fixationsmentioning
confidence: 97%
“…As an extreme example, study the responses to questions as in the Cognitive Reflection Test, with median response times typically above 30 seconds, and find differences depending on whether the questions elicited more or less intuitive responses.4 Achtziger and Alós-Ferrer (2014) applied the model to reinforcement and Bayesian updating in a belief updating task Spiliopoulos (2018). used the model to study win-stay, lose-shift vs. more sophisticated (cognitive) heuristics in a repeated game played against computer algorithms Ludwig et al (2020). applied it to heuristic decisions in probability judgments.…”
mentioning
confidence: 99%